Recurrent Cardiac Tamponade: An Unusual Presentation of Intrahepatic Cholangiocarcinoma. Issue 3 (April 2016) - Diaz, Liege I.; Corral, Juan E.; Arosemena, Leopoldo; Garcia‐Buitrago, Monica T.; Madrazo, Beatrice; Martin, Paul
Abstract : N/A: A 48‐year‐old Egyptian woman presented with 8 months of sharp right upper chest pain and weight loss. She was discovered to have an enlarged cardiac silhouette on chest x‐ray, and an echocardiogram revealed a large pericardial effusion with diastolic right atrial collapse. Pericardial window was done, and epithelial membrane antigen‐positive neoplastic cells were identified in the pericardial fluid. Computed tomography showed a 6‐cm hypermetabolic lesion on the liver segment IV, confirmed on biopsy to be a moderately differentiated adenocarcinoma consistent with intrahepatic cholangiocarcinoma.